THE IMPORTANCE OF EMBRYOTROPIC AUTOANTIBODS IN THE ASSESSMENT OF THE IMMUNE SYSTEM OF WOMEN WITH ADENOMYOSIS (World Bulletin of Public Health, 2024)
We observed perimenopausal women with adenomyosis; in order to assess the immunoreactivity of the body, embryotropic antibodies were determined in the blood serum using the ELIP test. The identified shifts in immunoreactivity are evidence of the readiness of trigger mechanisms in the implementation of newly formed foci of endometriosis. Probably, the solution to the problems of preventing the recurrence of internal endometriosis (adenomyosis) lies in both correcting the state of the immune system, taking into account reactivity, and the endocrinemetabolic adaptation-homeostatic reactions mediated by it in the female body.
Keywords: fetal autoantibodies; adenomyosis; perimenopause